2002
DOI: 10.1021/bi015734i
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Structure and Activity of Haloalkane Dehalogenase from Sphingomonas paucimobilis UT26: Evidence for Product- and Water-Mediated Inhibition,

Abstract: The hydrolysis of haloalkanes to their corresponding alcohols and inorganic halides is catalyzed by alpha/beta-hydrolases called haloalkane dehalogenases. The study of haloalkane dehalogenases is vital for the development of these enzymes if they are to be utilized for bioremediation of organohalide-contaminated industrial waste. We report the kinetic and structural analysis of the haloalkane dehalogenase from Sphingomonas paucimobilis UT26 (LinB) in complex with each of 1,2-dichloroethane and 1,2-dichloroprop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 25 publications
5
38
0
Order By: Relevance
“…The major catalytic domain of LinB belongs to the large and well-characterized ␣/␤-hydrolase fold superfamily of proteins, which characteristically carry out two-step hydrolytic reactions driven by a nucleophile (Asp) that is part of a catalytic triad and using an oxanion hole to stabilize the intermediate (69,114,117). LinB has been the subject of several crystallographic (92,123,166) and computational studies (32,33,69,122,130).…”
Section: Linb Haloalkane Dehalogenase Biochemistrymentioning
confidence: 99%
“…The major catalytic domain of LinB belongs to the large and well-characterized ␣/␤-hydrolase fold superfamily of proteins, which characteristically carry out two-step hydrolytic reactions driven by a nucleophile (Asp) that is part of a catalytic triad and using an oxanion hole to stabilize the intermediate (69,114,117). LinB has been the subject of several crystallographic (92,123,166) and computational studies (32,33,69,122,130).…”
Section: Linb Haloalkane Dehalogenase Biochemistrymentioning
confidence: 99%
“…This sequence-location difference of the catalytic pentad residues defines three evolutionary subfamilies of HLDs. 10 Two structures are known from evolutionary subfamily I (DhlA [11][12][13] and DppA 14 ), and four from subfamily II (DhaA, 15,16 LinB, [17][18][19][20] DbjA, 21 and Rv2578 22 ). Several structures include bound substrates, products, or covalent intermediates, which together with many kinetic studies, led to a detailed reaction mechanism for this enzyme class.…”
Section: Introductionmentioning
confidence: 99%
“…However, the activities of these mutants were still higher than that of LinB UT in both the first-and second-step dehalogenations, which suggested that one or more of the other five residues (T81, V112, T135, L138, and I253) uniquely found in LinB MI were also important for the high dehalogenation activity of LinB MI . To date, the crystal structure of LinB UT has been described (11)(12)(13)(14), whereas the crystal structure of LinB MI has not. To investigate how the seven residues that are different between LinB MI and LinB UT contribute to their different enzymatic properties, we performed site-directed mutagenesis and X-ray crystallographic studies of LinB MI and its seven point mutants, where each LinB MI -specific residue is mutated to the LinB UT -type residue (T81A, V112A, V134I, T135A, L138I, H247A, and I253M).…”
mentioning
confidence: 99%